Empowering minds, transforming lives - Montañez, Ma. Cristilina A.; Camilo, Rachel S.; Cabico, Luiscel Teofi; Cuevas, Aileen G. (Journal of Interdisciplinary Studies in Education, 2026)
This study evaluated a university-led community extension program using literature-based reading instruction to improve comprehension among children in conflict with the law (CICL) at a rehabilitation center for youth in Cebu, Philippines. Using a quasi-experimental design, significant gains were observed in lexical (t = 0.03) and critical (t = 0.01) comprehension across grades 0–3, 4–6, 7–8, and 11–12, whereas grades 9–10 showed no significant improvement. The program enhanced vocabulary and analytical skills but had a limited impact on interpretive and creative comprehension. The findings highlight the value of facilitator-supported instruction and call for more tailored strategies. This study affirms that reading is a rehabilitative tool and urges further research on long-term and socioemotional literacy factors.